2020
DOI: 10.1098/rsif.2020.0396
|View full text |Cite
|
Sign up to set email alerts
|

Agent-based simulation of collective cooperation: from experiment to model

Abstract: Simulation models of pedestrian dynamics have become an invaluable tool for evacuation planning. Typically, crowds are assumed to stream unidirectionally towards a safe area. Simulated agents avoid collisions through mechanisms that belong to each individual, such as being repelled from each other by imaginary forces. But classic locomotion models fail when collective cooperation is called for, notably when an agent, say a first-aid attendant, needs to forge a path through a densely packed group. We present a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…In this, the Optimal Steps Model is a classic model of pedestrian dynamics. For details, we refer to [ 62 ].…”
Section: Methodsmentioning
confidence: 99%
“…In this, the Optimal Steps Model is a classic model of pedestrian dynamics. For details, we refer to [ 62 ].…”
Section: Methodsmentioning
confidence: 99%
“…In this Letter, we argue that, even at the operational level, crowds in some dailylife circumstances display signs of anticipation that may elude the foregoing shortsighted models ; this will be exemplified by the recently studied response of a static crowd when crossed by an 'intruder' [15,16]. We purport to show that a minimal game theoretical approach, made tractable thanks to an elegant analogy between its mean-field formulation [17][18][19] and Schrödinger's equation [20,21], can replicate the empirical observations for this example case, provided that it accounts for the anticipation of future costs.…”
Section: Introductionmentioning
confidence: 91%
“…Several spatio-temporal scales, such as "local" and "global" spatial scales and "instant" and "short term" temporal scales, have been considered in the existing research. These studies believe that individuals prefer observing the local interactions with adjacent crowds, obstacles, and the environment to avoid collisions and their global distribution to obtain feasible routes [29]. Furthermore, the individual spatio-temporal cognitive processes are generally treated as a sequence of independent fragments of the "instant" scale, which assumes present situations greatly impact the route choice, and it has also been confirmed that the effect of the "short term" is that individual current decisions are related to the episodic memory in the near past [28].…”
Section: Multiple Spatio-temporal Scales' Characteristicsmentioning
confidence: 99%